Kepastian Hukum Akta Jual Beli PPAT atas Sertifikat Hak Milik Nomor 710/Desa Kuta: Analisis terhadap Putusan Pengadilan Tinggi Denpasar Nomor 35/Pdt/2021/ PT. DPS - Raihan Daffi Nauli Siregar; hasim purba; tony (Jurnal Hukum Lex Generalis, 2026)
Legal certainty in the preparation of Sale and Purchase Deeds (AJB) by Land Deed Officials (PPAT) is a crucial aspect in ensuring the validity of land rights transfers. This study examines Certificate of Ownership No. 710/Kuta Village based on the Denpasar High Court Decision No. 35/PDT/2021/PT DPS using a normative juridical method and statutory approach. The results indicate that violations of formal requirements by PPAT result in the deed being declared invalid and undermine legal certainty. Furthermore, PPAT liability includes both administrative and civil aspects, making compliance with legal procedures essential to ensure the validity and legal certainty of a deed.